Influence of smoking rate on ultrafine particle emission of cigarette smoke - Arinto Y.P Wardoyo; Dionysius J.D.H Santjojo; Tintrim Rahayu; Saraswati Subagyo (The East Java Biological Society, 2018)
Ultrafine particles have been attached the attention for researchers due to their impacts on human health. Ultrafine particles can be emitted fromburning process, such as forest burning, agriculture waste burning, cigarette, etc. In this study, ultrafine particles produced by cigarette smokes hasbeen investigated as a function of smoking rate. The samples consisted of different types of Indonesia cigarette called Kretek cigarette. Thequantification of emission factors was conducted by the burning of the cigarette samples, then the smoke that was sucked with a different flow rateusing an adjustable pump. The flow rate was chosen to correspond as close as the variation of the rate that people smoke. The measurements ofultrafine concentrations were carried out using an ultrafine particle counter P-Trak TSI 8525 capable of measuring particles with the diameter in therange of 20 to 1000 nm. The results showed that the emission factor of ultrafine particles significantly depended on the smoking rate. A highersmoking rate produced higher average ultrafine particle emission factor.